Ethical Improprieties During the Procurement Stage in The Malaysian Construction Industry - Siti Zahidah Md Yusuf; Zainab Mohmad Zainordin; Zarina Alias; Nurul Asra Abd Rahman (Online Journal for TVET Practitioners, 2025)
This paper examines critical ethical challenges in procurement within Malaysia’s construction industry, focusing on issues like transparency lapses, bid rigging, bribery, and collusion. These unethical practices are attributed to weak systems, unclear ethical standards, and inadequate awareness of regulations, particularly in complex procurement processes. The study evaluates the determinants, consequences, and preventive measures for such violations, emphasizing the significant economic, reputational, and regulatory impacts. Data was collected from construction stakeholders, including developers, consultants, contractors, and government agencies, using a quantitative survey methodology. Results reveal that ineffective management, poor legislation, and weak governance are primary contributors to unethical behavior. Major consequences include a pervasive culture of bribery and corruption. Recommended preventive measures include strict penalties such as fines, suspensions, blacklisting, and enforcing severe legal actions like imprisonment to uphold integrity and transparency.